(untitled) (Palíndromo, 2018)
Helio Oiticica’s work is vast, diverse, based on processes and connected with concepts as subject and body. The ideas supported by the artist are recognized as the poetics of gesture and seems to be linked with the contemporaneity for several reasons like the horizontal relation between artist and participant, the interaction that overcomes contemplation, passivity and manipulation and the deinstitutionalization of artistic processes, pro-moting discussions about art, politics and society. This article discusses the environmental character developed by Oiticica in his works in order to motivate artistic practices connected with their contexts and open to bodily experiences, collective constructions and the gesture itself. The proposal of this article is to present a poetic possibility as one of the ways in which contemporaneity can be developed.